Perbedaan Hasil Belajar Siswa Menggunakan Model Pembelajaran Brainstorming dan Model Pembelajaran Everyone is A Teacher Here Kelas X SMK Negeri 1 Patumbak T.A. 2021/2022 - Aqila Zahra; Nurjanah (Jurnal Pendidikan Ekonomi Undiksha, 2026)
This study aims to determine the differences in student learning outcomes using the Brainstorming learning model and the Everyone Is A Teacher Here learning model in class X of SMK Negeri 1 Patumbak. This type of research is quantitative research that is experimental in nature. This research was conducted at SMK Negeri 1 Patumbak. The population of this study was all students of class X OTKP consisting of 4 (four) classes with a total of 144 students. From this population, the samples were class X OTKP - 1 36 students as a class using the Brainstorming model and class X OTKP - 2 36 students as a class using the Everyone Is A Teacher Here model. And using a random sampling type. The data instrument used was a multiple-choice learning outcome test. Based on the results of the study, it can be concluded that the Brainstorming class had an average score of 77.96 with a standard deviation of 8.118 and the Everyone Is A Teacher Here class had an average score of 55.93 with a standard deviation of 12.01 while the combined deviation was 10.25. And the results of the hypothesis test calculation obtained the results of t count = 8.597 and t table = 1.999 obtained from the t distribution list, with t count > t table then HO is rejected, so the alternative hypothesis Ha is accepted which means that there is a difference in the learning outcomes of students' archiving taught with the Brainstorming learning model and the Everyone Is A Teacher Here model in class X OTKP - 1 and X OTKP - 2 SMK NEGERI 1 PATUMBAK Academic Year 2021/2022.